INTRODUKSI TEKNOLOGI PAKAN UNTUK MENINGKATKAN PRODUKSI DAN KUALITAS SUSU KERBAU MURRAH DI NAGARI KAPAU KECAMATAN TILATANG KAMANG KABUPATEN AGAM - Elly Roza; Salam N. Aritonang; Yulia Yellita; Rizqan Rizqan; Elihasridas Elihasridas; Ade Rakhmadi (LPPM Universitas Andalas, 2022)
The Murrah buffalo is a breed of dairy-type river buffalo that has better milk production than the Mud buffalo. In West Sumatra, buffaloes are generally kept traditionally and the feed provided is low-quality field grass without providing concentrate so that productivity has not shown good results. This increase in productivity can be done through improving maintenance management and improving the quality of the feed given to buffaloes. Community service is an activity that aims to provide knowledge in technological innovation to breeders in the form of providing probiotics and the use of local forage feeds, especially cassava leaves as supplementary feed for buffaloes to increase production and quality of buffalo milk in order to increase farmers' income, while the specific target is expected to foster community self-reliance. in an effort to use local forage as animal feed. The method applied is counseling, training/pilots and discussion are the best ways to transfer knowledge and technology to farmers, while guidance and coaching can be done periodically through coordination with the head of the Kelok Rambai Cattle Farmer's group, Nagari Kapau, Tilatang Kamang District, Agam Regency. is the only livestock group in Kab. Agam who raises Murrah buffalo as a producer of curd. The results obtained were an increase in milk production 3.25 vs 4.75 l/day and milk quality: fat 5.47 vs 6.26%, Protein 4.35 vs 5.60%, SNF 10.76 vs 11.85% and water content 82.20 vs 81.75%. The conclusion of this activity is that the provision of probiotics and cassava leaf pellet supplement feed can increase the production and quality of Murrah buffalo milk and increase the income of farmers.